Comparing functioning in spinal cord injury and in chronic spinal pain with two ICF-based instruments: WHODAS 2.0 and the WHO minimal generic data set covering functioning and health. (July 2019) - Tarvonen-Schröder, Sinikka; Kaljonen, Anne; Laimi, Katri
Objective: To investigate whether the two briefest validated ICF-based (International Classification of Functioning, Disability and Health) tools can detect differences between different spinal conditions. Design: Cross-sectional study. Setting: University hospital rehabilitation clinic. Subjects: A total of 84 patients with spinal cord injury and 81 with chronic spinal pain. Main measures: Disability evaluated using self-reported and proxy 12-item WHODAS 2.0 ((World Health Organization Disability Assessment Schedule), and physician-rated WHO minimal generic data set covering functioning and health. Findings: The two measures used showed severe disability in both patient populations, those with spinal cord injury (mean age 47.5 years, SD 13.2) and those with chronic spinal pain (mean age 47.2 years, SD 9.5), WHODAS patient sum being 18.4 (SD 9.6) versus 22.0 (SD 9.0), P < 0.05, and the WHO generic data set 15.6 (SD 4.4) versus 14.2 (SD 3.7), P < 0.01, respectively. Correlations between patient and proxy ratings and between the two disability scales were mostly strong. Severe restrictions were found in the working ability of both the populations, in mobility of patients with spinal cord injury and in pain function of patients with chronic spinal pain. In this tertiary clinic patient population, patients with spinal pain perceived more problems in emotional and cognitive functions, and in participation than patients with spinal cord injury. Conclusions: Both scales were able to find differences between two patient populations with severe disability.